The handbook of international marketing communications (Oxford, UK ; Malden, MA : Blackwell, 1999)
This book is about: General overview: Issues and concepts; Aspects of international marketing communications; ...
Keywords: Marketing; Export marketing; Marketing; Export marketing; Advertising; Communication in marketing; Communication, International